Efficacy and safety of sofosbuvir plus daclatasvir in hemodialysis patients with genotype 1b or 2a hepatitis C virus infection: a single-arm, prospective real-world study - Wang, Kaili; Yao, Hongyu; Zhou, Xia; Liu, Hongling; Zhao, Jun (Frontiers in Medicine, 2025)
Background/aimsThis investigation assessed the clinical outcomes and adverse effects of combination therapy using sofosbuvir (SOF) and daclatasvir (DCV) among dialysis-dependent patients infected with hepatitis C virus (HCV) genotypes 1b or 2a in real-world settings.MethodsWe conducted a prospective, single-arm interventional trial comprising 16maintenance hemodialysis patients (14 with HCV-1b, 2 with HCV-2a). Participants received SOF-DCV combination therapy over 24 weeks with monitoring at weeks 4, 12, and 24 during treatment, plus a follow-up assessment 12 weeks post-treatment completion. The primary outcome measure was sustained virologic response at 12 weeks post-treatment (SVR12). Secondary endpoints included therapeutic tolerance and safety profiles.ResultsAll 16 participants completed the prescribed treatment regimen. Demographic characteristics revealed a mean age of 57.0 years, male predominance (75%), average dialysis duration of 7.0 years, and mean body weight of 63.0 kg. Five patients (31.3%) had compensated cirrhosis. Liver function parameters remained stable throughout the study period. Rapid virologic response (RVR) was documented in 87.5% (14/16) of participants, while end-of-treatment response (ETR) and SVR12 were both achieved in 93.8% (15/16) of cases. All cirrhotic patients (5/5) ultimately attained SVR12. The therapeutic regimen demonstrated favorable tolerability, with no treatment discontinuations due to adverse events. One participant was lost to follow-up. APRI scores significantly decreased from baseline (0.56) to week 24 (0.20, p < 0.001). Reported adverse reactions included headache, fatigue, nausea (each 6.3%), and anemia (18.8%).ConclusionThe 12-week SOF-DCV combination demonstrated robust therapeutic efficacy and acceptable safety profiles in hemodialysis patients infected with HCV genotypes 1b or 2a, including those with compensated cirrhosis.